2021
DOI: 10.1038/s42003-021-02935-z
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic models developed for plains zebras predict age in domestic horses and endangered equids

Abstract: Effective conservation and management of threatened wildlife populations require an accurate assessment of age structure to estimate demographic trends and population viability. Epigenetic aging models are promising developments because they estimate individual age with high accuracy, accurately predict age in related species, and do not require invasive sampling or intensive long-term studies. Using blood and biopsy samples from known age plains zebras (Equus quagga), we model epigenetic aging using two appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
37
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
2
1

Relationship

4
3

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 112 publications
4
37
0
Order By: Relevance
“…We tested whether phenotypic divergence occurred via epigenetic modifications, specifically DNA methylation, which alter gene expression without changing the DNA sequence (Razin & Riggs, 1980). Over 29,000 probes aligned to our genome, consistent with other mammalian studies (Larison et al, 2021; Pinho et al, 2021; Schachtschneider et al, 2021; Sugrue et al, 2021), and a robust epigenetic clock was generated (Figure 1). The differential methylation between island-mainland populations showed a remarkable overlap between enriched pathways and measured phenotypic differences.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…We tested whether phenotypic divergence occurred via epigenetic modifications, specifically DNA methylation, which alter gene expression without changing the DNA sequence (Razin & Riggs, 1980). Over 29,000 probes aligned to our genome, consistent with other mammalian studies (Larison et al, 2021; Pinho et al, 2021; Schachtschneider et al, 2021; Sugrue et al, 2021), and a robust epigenetic clock was generated (Figure 1). The differential methylation between island-mainland populations showed a remarkable overlap between enriched pathways and measured phenotypic differences.…”
Section: Discussionsupporting
confidence: 84%
“…These epigenetic clocks, while they can predict chronological age (Jasinska et al, 2021;Lu et al, 2021;Prado et al, 2021;Raj et al, 2021;Schachtschneider et al, 2021), have also been shown to be elevated in inbred individuals, suggesting that inbreeding can lead to aging at a faster rate compared to non-inbred individuals (Larison et al, 2021). Likewise, metabolic syndrome in humans (i.e., hypertension, obesity) also results in increased epigenetic aging (Lee & Park, 2020;Nannini et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Marttila et al 11 observed that age-associated DNA hypermethylation seems to originate from programmed developmental changes while DNA hypomethylation could result from environmental in uences 11 . Furthermore, DNAm pro les in several species have been demonstrated to predict individuals' biological age, known as epigenetic clocks [12][13][14][15][16][17][18][19][20][21][22][23] . Recently, Caulton et al 13 reported a prediction accuracy of 0.95 for epigenetic clocks based on DNAm in a dairy herd.…”
Section: Introductionmentioning
confidence: 99%